2018
DOI: 10.4103/0366-6999.237398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphatidylinositol-3-Kinase/Protein Kinase B-Mammalian Target of Rapamycin Signaling Pathway on the Neuropathic Pain Complicated by Nucleoside Reverse Transcriptase Inhibitors for the Treatment of HIV Infection

Abstract: Background:Nucleoside reverse transcriptase inhibitors (NRTIs) are the earliest and most commonly used anti-human immunodeficiency virus drugs and play an important role in high active antiretroviral therapy. However, NRTI drug therapy can cause peripheral neuropathic pain. In this study, we aimed to investigate the mechanisms of rapamycin on the pain sensitization of model mice by in vivo experiments to explore the effect of mammalian target of rapamycin (mTOR) in the pathogenesis of neuropathic pain caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…D4T increased the expression and activity of mTORC1 in the spinal cord by activating the Akt/mTOR signaling pathway. In contrast, rapamycin can reverse D4T-induced mechanical hyperalgesia by inhibiting the mTOR signaling pathway and reducing mTORC1 activity, suggesting that the Akt/mTOR signaling pathway is involved in HRNP (Cheng & Wu, 2018).…”
Section: Other Signaling Pathwaysmentioning
confidence: 95%
“…D4T increased the expression and activity of mTORC1 in the spinal cord by activating the Akt/mTOR signaling pathway. In contrast, rapamycin can reverse D4T-induced mechanical hyperalgesia by inhibiting the mTOR signaling pathway and reducing mTORC1 activity, suggesting that the Akt/mTOR signaling pathway is involved in HRNP (Cheng & Wu, 2018).…”
Section: Other Signaling Pathwaysmentioning
confidence: 95%
“…Mitochondrial toxicity can lead to the inhibition of late stages of autophagy mediated by active mTORC1 signaling, as shown for zidovudine (NRTI) in myocytes [137]. Another study demonstrated that stavudine (NRTI) could activate mTORC1 signaling in a mouse model of peripheral neuropathic pain [138]. Treatment with rapamycin attenuates persistent neuropathic pain in mice.…”
Section: Mtorc1 Pathway In Hiv-1-related Diseasesmentioning
confidence: 95%
“…The use of inhibitors such as SH-6 [ 96 ] ( Figure 22 ) demonstrated the involvement of PKB/Akt in mechanical hypersensitivity [ 97 ]. More recently, Cheng et al studied the role of phosphatidylinositol 3-kinase (PI3K)/PKB/mTOR signaling pathway in neuropathic pain caused by nucleoside reverse transcriptase inhibitors in HIV treatment [ 98 ].…”
Section: Protein Kinases a G And C (Agc) Groupmentioning
confidence: 99%